1997
DOI: 10.1002/(sici)1097-0347(199710)19:7<589::aid-hed5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy following neck dissection and parotidectomy for metastatic malignant melanoma

Abstract: Background Regional recurrence remains a problem in the management of patients with metastatic malignant melanoma in the cervical lymph nodes and parotid. In this study, the influence of the number of positive nodes, extracapsular spread, and the use of adjuvant radiotherapy on regional control and survival were analyzed. Methods A non‐randomized, prospectively documented series of 143 patients with histologically positive nodes in the neck or parotid was analyzed. There were 152 dissected necks or parotids: 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 11 publications
2
60
1
5
Order By: Relevance
“…Two randomized controlled trials [338,339] confirmed six retrospective cohort studies [336,337,340,341,343,345] in showing significantly higher locoregional control rates in patients with lymph node metastases undergoing postoperative adjuvant radiation therapy of the affected lymph node basins. In Burmeister et al, 34 of 127 patients without radiation therapy sustained locoregional lymph node recurrence, whereas in the patient group subjected to adjuvant radiation therapy, 20 patients suffered recurrence within the lymph node basin.…”
Section: Level Of Evidence 2bmentioning
confidence: 78%
See 2 more Smart Citations
“…Two randomized controlled trials [338,339] confirmed six retrospective cohort studies [336,337,340,341,343,345] in showing significantly higher locoregional control rates in patients with lymph node metastases undergoing postoperative adjuvant radiation therapy of the affected lymph node basins. In Burmeister et al, 34 of 127 patients without radiation therapy sustained locoregional lymph node recurrence, whereas in the patient group subjected to adjuvant radiation therapy, 20 patients suffered recurrence within the lymph node basin.…”
Section: Level Of Evidence 2bmentioning
confidence: 78%
“…Systematic search of the literature de-novo: [336][337][338][339][340][341][342][343][344][345] Strength of consensus: 100%…”
Section: Level Of Evidence 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly we were able to show a significant reduction in recurrence in patients who received adjuvant radiation, especially those with N3 disease. O'Brien (O'Brien et al, 1997) was also able to demonstrate a reduction in recurrence but this fell short of statistical significance (just). Our overall rerecurrence rate of 28% in patients who did not receive adjuvant radiation is similar to the figure reported by O'Brien et al (O'Brien et al, 1997) and lower than many reports (O'brien et al, 1997).…”
Section: Wwwintechopencommentioning
confidence: 90%
“…O'Brien (O'Brien et al, 1997) was also able to demonstrate a reduction in recurrence but this fell short of statistical significance (just). Our overall rerecurrence rate of 28% in patients who did not receive adjuvant radiation is similar to the figure reported by O'Brien et al (O'Brien et al, 1997) and lower than many reports (O'brien et al, 1997). The dramatic decrease in recurrence in our patient both with N3 disease and regional disease overall is in agreement with the findings of Ang and colleagues (Ang et al, 1994) from the MD Anderson unit in Texas.…”
Section: Wwwintechopencommentioning
confidence: 91%